Interactive Web service via satellite to the home. - Choi, Hyoung-Kee (IEEE Communications magazine)
The satellite distribution of digital broadcast signals to the home has become widespread in the last seven years, delivering hundreds of television channels. We we have also seen other services appear, such as Direct PCTM where data is broadcast. This service may be used to deliver information like stock quotes to a large number of users, or information such as Web pages may be requested by a single user. In the latter case, however, a return path is needed from the end user to the service provider in order to provide the specific information requested by the user. In services offered today this information is usually provided by a terrestrial return link, most often a telephone line. While a telephone line with a modem is adequate in most cases, it has the drawback of tying up an existing telephone line for a considerable amount of time for very little data transmission, or requiring an additional line. Furthermore, in many parts of the world a telephone line may not be readily available. In these cases a satellite return link may be a viable option using VSATs. We describe an investigation and simulation of a return path VSAT link designed specifically for delivery of Web traffic requests to a base station and thence via a terrestrial link, using the Internet, to a Web server. The focus in this work is on the MAC protocol to support such a satellite channel and on modeling the whole service from traffic generation through transport, network, and MAC layers to the physical channel